Design and Performance Analysis of New Tooth Profile of Harmonic Drive - Yu Jinbao; Fan Yuanxun (Jixie chuandong)
Based on the basic profile of the tool,according to the tooth profile normal method to obtain the flexible gear tooth profile,then the conjugated rigid wheel profile is solved by the envelope theory. Using the data processing ability and graphics display function of the Matlab software,the parameters and shape of the flexion wheel tooth profile is displayed by programming,and the new tooth profile meshing performance is judged,the theoretical meshing arc length and the number of pairs of tooth meshing at the same time are calculated. The backlash value of every point in the flexible gear profile to rigid wheel tooth profile is solved,then the minimum backlash value is found out and rule analysis is carried out,the rigid flexible wheel does not engage in meshing interference is verified. The deflection of the gear teeth caused by the flexible wheel deformation is analyzed,and using the method of modifying displacement coefficient to solve the meshing problem caused by the flexible wheel deformation,and the three-dimensional tooth profile of the rigid wheel is designed to avoid meshing interference without changing the parameters of the flexible wheel tooth profile.